Screening of Anxiety and Depression in Patients With Fibromyalgia From 18 to 65 Years Old and Its Relationship With the Severity of Fibromyalgia and Quality of Life (2018)
Objective: To identify the relationship between anxiety and depression with the severity of fibromyalgia and quality of life in patients aged 18 to 65 years, clinic of rheumatology of Barranquilla. Methods: Observational, descriptive, comparative cross-sectional study. Patients with fibromyalgia who attend the external consultation of rheumatology will be surveyed. The questionnaires to be applied are the Fibromyalgia Impact Questionnaire Revised (Spanish version), Health Questionnaire SF-36, Patient Health Questionnaire and a Scale of 7 questions for generalized anxiety disorder. The data collected in this descriptive study will be analyzed by means of frequency and association measures. The analysis of association between sociodemographic factors and clinical characteristics will be carried out with bivariate analysis and the comparison of qualitative or categorical variables will be done through the analysis of variance, to compare variables of ordinal type and variables of type ratio. Results: 34.2% of the patients did not present anxiety whereas 83.6% of the patients had some degree of depression. 50% of the patients had moderate, severe and extreme degrees of depression. An association was found between severity of fibromyalgia with anxiety, depression and quality of life (p <0.05). Conclusion: A directly proportional relationship was found between the severity of depression and anxiety and the severity of FM. An elevated score in the FIQR, lower weighted scores for quality of life in the participants, in addition to greater severity in the scales GAD - 7 and PHQ - 9, all score to lower quality of life.